PENDAMPINGAN DIGITLISASI KEUANGAN MELALUI TRANSFER BANK BAGI ANGGOTA KSPPS PRINGGODANI TANGGUH DEMAK - Liza Ariyanti; Rizka Naza Nayshila; Eni Kusrini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The advancement of digital technology in the financial sector has encouraged service transformation within financial institutions, including Islamic cooperatives. However, the low digital literacy of cooperative members remains a challenge, as most transactions are still conducted in cash, causing delayed payments, non-performing financing, and weak administrative recording. The financial digitalization mentoring program through bank transfers at KSPPS Pringgodani Tangguh Demak aimed to enhance members’ understanding of digital banking services and improve financial governance. The mentoring was carried out simply and practically through direct guidance during routine transactions, home visits, and assistance in using transfer receipts as verification instruments. The results show improved digital literacy, behavioral shifts from cash to non-cash transactions, greater efficiency, and stronger transparency and accountability through digital proof of transfers. Personal approaches and member testimonials also increased confidence and collective motivation in building a digital culture within the cooperative. Overall, this program positively impacts members and strengthens KSPPS Pringgodani Tangguh Demak’s institutional capacity to become a modern and adaptive Islamic cooperative aligned with the national Islamic financial inclusion agenda.